Peran Perhimpunan Bangsa-Bangsa Asia Tenggara dalam Menanggulangi Eksploitasi Perempuan dan Anak - Anthony Steven; Dorantes Wijaya; Dave David Tedjokusumo (Jurnal Syntax Admiration, 2024)
Human trafficking, especially the exploitation of women and children, is a serious problem that threatens humanity in the ASEAN region. The Association of Southeast Asian Nations (ASEAN) has an important role in tackling this phenomenon. This research aims to analyze ASEAN's role in tackling human trafficking, with a focus on the exploitation of women and children, as well as to identify challenges and provide recommendations for improvement. The research method used is the normative juridical method, which examines various legal materials as the main basis for answering research problems. A statutory and conceptual approach is used to examine relevant legal instruments and examine concepts related to human trafficking, human rights, and the protection of women and children. Data was collected through document studies and secondary literature, then analyzed qualitatively to evaluate ASEAN's role and effectiveness in tackling human trafficking. The research results show that ASEAN has adopted various legal instruments, including the ASEAN Convention Against Trafficking in Persons (ACTIP), but implementation and coordination between member countries is still a major challenge. The role of civil society and non-governmental organizations is also important in supporting efforts to combat human trafficking in the ASEAN region. Recommendations are suggested to strengthen policy implementation, increase regional cooperation, and strengthen protection for victims, especially women and children.